If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(6 + 2x) = 5(5 + 3x) (6 * 6 + 2x * 6) = 5(5 + 3x) (36 + 12x) = 5(5 + 3x) 36 + 12x = (5 * 5 + 3x * 5) 36 + 12x = (25 + 15x) Solving 36 + 12x = 25 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 36 + 12x + -15x = 25 + 15x + -15x Combine like terms: 12x + -15x = -3x 36 + -3x = 25 + 15x + -15x Combine like terms: 15x + -15x = 0 36 + -3x = 25 + 0 36 + -3x = 25 Add '-36' to each side of the equation. 36 + -36 + -3x = 25 + -36 Combine like terms: 36 + -36 = 0 0 + -3x = 25 + -36 -3x = 25 + -36 Combine like terms: 25 + -36 = -11 -3x = -11 Divide each side by '-3'. x = 3.666666667 Simplifying x = 3.666666667
| 9-14=x_12 | | 35x^2-y^3= | | 8x+10=.5(12x+40) | | -2x+y=2 | | -6x+x=9 | | -5x+8=31 | | 7-4x=35 | | 3x^2-2=-3x | | x(2)-100=0 | | S*3-2=9 | | (-b-6)5= | | x=x^2+x-3 | | 2x(2)+11x-6=0 | | (6+7)x= | | .25x-1=7 | | 8x-56=0 | | 2[p-(3p+7)+1]=2(p+6) | | 2x(7+2x)=x(x+23) | | (3x-6)=15 | | 3[4-(-4)]= | | 5(4*4-6)-5(-3*-3*-3+16)= | | x^6-25x^4-10x^3-10=0 | | r^4+3r^3+5r^2+3r+1=0 | | 7.11=2*3.14r | | [t-(4T+7)+5]=2(t+2) | | 252=(x+2)(2x+1) | | z^2+16z+52=0 | | 519.84=x(x+22.8) | | x+3x+6x-14=180 | | 8(7.58+8+2)=7.58(7.58+3(7.58)) | | 8(8+x+12)=x(x+3x) | | 4x+15=5x-11 |